Highway Construction in Hong Kong: Engineering Complexity, Environmental Governance, and Infrastructural Megaprojects in a Dense Urban Environment (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This article critically analyses the evolution, governance, and socio-environmental ramifications of highway construction in Hong Kong, a global metropolis distinguished by its extreme population density, intricate topography, and rigorous regulatory frameworks. Using policy papers, environmental impact assessments, project reports, and legislative records from 1974 to 2025, I show that Hong Kong's highway development is a good example of "compressed infrastructural modernity." In this model, engineering innovation, environmental protection, and fiscal accountability are always being negotiated in situations where space is limited and the public is watching. The analysis examines the evolution from the territory's inaugural motorway, Tuen Mun Road (1974–1983), to current megaprojects such as the Central Kowloon Route and the Tsing Yi–Lantau Link, emphasising three salient characteristics: (1) the institutionalisation of environmental assessment as a mandatory framework for project design; (2) the advent of digital and automated construction technologies as solutions to labour shortages and safety requirements; and (3) ongoing conflicts between cost Limitations encompass constrained access to internal governmental discussions and dependence on publicly available EIA documents. The results show that Hong Kong's highway sector has become very technically advanced, but it still has trouble predicting cost overruns and working together with other agencies.